2D organic single crystals: Synthesis, novel physics, high-performance optoelectronic devices and integration. (November 2021) - Zhang, Linglong; Mehedi Hasan, Md; Tang, Yilin; Raza Khan, Ahmed; Yan, Han; Yildirim, Tanju; Sun, Xueqian; Zhang, Jian; Zhu, Jiaqi; Zhang, Yupeng; Lu, Yuerui
Abstract: In the last decade, two-dimensional organic single crystals (2D OSCs), defined as a class of ultrathin crystals with atomic or molecular level thickness and micrometer-scale-lateral dimension, has emerged as a rising star due to ultrathin feature, high crystallinity, low-structure symmetry, larger material library, diverse processing technique and excellent flexibility, etc . Due to these advantages, 2D OSCs offer exciting application prospects for flexible electronics, optoelectronics, sensing, energy harvesting, biology and medicine, etc . However, it is still challenging to synthesize large-area highly crystalline 2D OSCs as well as investigate their intrinsic properties and structure–property relationships. Herein, we first treat the growth techniques of 2D OSCs carefully and then discuss their novel physics and optoelectronic properties at the 2D limit. A significant effort has been made in evaluating the latest advances in high-performance devices applying 2D OSCs and corresponding heterostructures. In terms of practical applications, their integrations and device arrays are discussed. Furthermore, we point out several important research directions of 2D OSCs and corresponding heterostructures. Finally, the state-of-the-art challenges and future opportunities that include the investigation and application of 2D OSCs have been presented, which will provoke more researchers to come into this field.